Midlife Crisis Long-Term Psychological Effects of Fatherlessness: A Fiqh Hadhanah Perspective (Case Study in Temanggung) - Na’imin, Na’imin; Mafiah, Yeni (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2024)
Fatherlessness is a condition where a father does not play a significant role in the upbringing of his child. The impact of fatherlessness can be very significant even when a person who experiences it reaches middle age, also known as midlife crisis. This study aims to reveal how midlife crisis can be said to be a long-term psychological effect of fatherlessness. As well as looking from the perspective of fikih hadhanah about the fatherless phenomenon. The method used in this research is a descriptive qualitative method with a case study approach, with a sample of two cases of middle-aged adults, with a fatherless background in Temanggung Regency. As for the data collection method, the author uses interviews, observations and literature reviews. The results of this study indicate that there is a correlation between midlife crisis and the fatherless phenomenon. A person with a fatherless experience in the past can cause a person to experience midlife crisis, but this does not mean that fatherless is the only cause of midlife crisis because there are several other factors that influence it. This research is expected to add scientific contributions in the field of Islamic family law and also family psychology. Fatherless merupakan suatu kondisi dimana seorang ayah tidak memiliki peran yang maksimal dalam pengasuhan anaknya. Faktor-faktor yang menyebabkan fatherless di Indonesia meliputi kematian ayah, perceraian orang tua, atau ayah yang tidak bertanggung jawab. Penelitian ini bertujuan untuk mengungkap bagaimana seseorang dapat mengalami midlife crisis sebagai efek psikologis jangka panjang akibat fatherless. Serta melihat dari perspektif fikih hadhanah tentang fenomena fatherless tersebut. Metode yang digunakan dalam penelitian ini adalah metode deskriptif kualitatif dengan pendekatan case study, dengan sample dua kasus orang dewasa paruh baya, dengan latarbelakang fatherless di Kabupaten Temanggung. Adapun metode pengumpulan datanya penulis menggunakan metode wawancara, observasi dan tinjauan literatur. Hasil penelitian ini menunjukkan bahwa ada korelasi antara midlife crisis dengan fenomena fahterless. Seseorang dengan pengalaman fatherless di masa lalu dapat mengakibatkan seseorang tersebut mengalami midlife crisis, namun tidak berarti fatherless ini menjadi satu-satunya penyebab terjadinya midlife crisis karena ada beberapa faktor lain yang turut berpengaruh. Penelitian ini diharapkan dapat menambah kontribusi ilmiah di bidang hukum keluarga Islam dan juga psikologi keluarga.